2014
DOI: 10.1371/journal.pone.0099735
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Novel Protein Complex Containing ASIC1a and GABAA Receptors and Their Interregulation

Abstract: Acid-sensing ion channels (ASICs) belong to the family of the epithelial sodium channel/degenerin (ENaC/DEG) and are activated by extracellular protons. They are widely distributed within both the central and peripheral nervous systems. ASICs were modified by the activation of γ-aminobutyric acid receptors (GABAA), a ligand-gated chloride channels, in hippocampal neurons. In contrast, the activity of GABAA receptors were also modulated by extracellular pH. However so far, the mechanisms underlying this intermo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 23 publications
2
10
0
Order By: Relevance
“…Protons are considered to be neurotransmitters regulating synaptic plasticity in the lateral amygdala [ 5 ]. In spite of growing evidence indicating that the density of ASICs is substantially higher in GABAergic interneurons than in glutamatergic cells [ 17 ] and recent demonstration of functional crosstalk between ASICs and GABA A -receptors [ 10 , 11 ], the possible involvement of ASICs in the regulation of GABAergic transmission remained unclear. In our work we present evidence for the first time that ASICs play a functional role at hippocampal GABAergic synapses.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Protons are considered to be neurotransmitters regulating synaptic plasticity in the lateral amygdala [ 5 ]. In spite of growing evidence indicating that the density of ASICs is substantially higher in GABAergic interneurons than in glutamatergic cells [ 17 ] and recent demonstration of functional crosstalk between ASICs and GABA A -receptors [ 10 , 11 ], the possible involvement of ASICs in the regulation of GABAergic transmission remained unclear. In our work we present evidence for the first time that ASICs play a functional role at hippocampal GABAergic synapses.…”
Section: Discussionmentioning
confidence: 99%
“…Functional interaction between ASICs and GABA A -receptors in isolated neurons has been recently demonstrated [ 10 , 11 ]. Activation of GABA A -receptors strongly changed ASIC-currents amplitude and pharmacological sensitivity [ 10 ], and the effect was blocked by antagonists of GABA A receptors [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Still, functional crosstalk between ASICs and GABA A receptors has been previously reported in isolated neurons [8]. …”
mentioning
confidence: 99%
“…Such an assumption is indirectly confirmed by the fact that amyloride, another blocker of protonactivated channels, influences considerably the effects induced by application of exogenous GABA [6,7] and GABA-mediated PSCs [8]. Recently, it was found that functional interaction between GABA A receptors and ASIC1a channels is quite possible; a protein complex including both abovementioned receptors has been identified [9].…”
Section: Resultsmentioning
confidence: 91%